A 21-year retrospective histopathological evaluation of cysts and tumours associated with impacted teeth - Mohammed, Muhanad Hashim Salman (My University, 2018)
Background Odontogenic cysts and tumours may be observed in association with impacted teeth. There are no published reports on the histopathological characterisation of cysts and tumours associated with impacted teeth in South Africa. This study aims to determine the relative frequencies and the clinico-pathological features of these lesions in a South African population sample, and to compare the data with information available in the literature. Methods The histopathology records of all specimens associated with impacted teeth were collected over a 21-year period from 1996 to 2016 from the files of the Department of Oral Pathology, School of Oral Health Sciences at the University of the Witwatersrand. Clinical data and histological diagnoses were reviewed and analysed. Results Out of a total of 24,542 pathology specimens, 407 (1.7%) specimens were associated with impacted teeth in 390 patients. Pathological lesions were diagnosed in 389 (95.6%) cases while 18 (4.4%) specimens represented non-pathological dental follicular tissue. The median patient age was 24 years (3-88 years) with males accounting for 64.9% of the patients. The 11-20 year age group showed the highest overall frequency of pathological lesions associated with impacted teeth, while the 41-50 year age showed the lowest frequency. Dentigerous cyst was the most commonly diagnosed lesion accounting for 63.4% and 43% of all lesions v diagnosed in males and females respectively. No significant association was found between the age of the patient and the biological potential of lesions associated with impacted teeth. Conclusions The frequency of histopathological diagnoses associated with impacted teeth significantly reduces with an increase in age. The findings of this study show similar trends to some previously published reports from other geographic areas. The information gathered in this study provides a local data base of the frequencies of odontogenic cysts and tumours associated with impacted teeth which may assist clinicians in formulating differential diagnoses.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Science in Dentistry. School of Oral Health Sciences, Faculty of Health Sciences University of the Witwatersrand, South Africa Johannesburg, 2018.
Keywords: Odontogenic Cysts